Solubilization and Controlled Release Strategy of Poorly Water-Soluble Drugs - M. A. Peña (Pharmaceuticals, 2022)
The processes of solubilization and controlled release of drugs that are poorly soluble in water are highly relevant in drug preformulation studies in pharmaceutical development [...]